Disseminated juvenile paracoccidoidomycosis evolving with portal hypertension: a case report (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2024)
Introduction: Juvenile paracoccidioidomycosis (PCM), a disease caused by fungi of the genus Paracoccidioides, requires high clinical suspicion, as a range of differential diagnoses are possible. Case report: This report describes a patient diagnosed with juvenile PCM who, due to low adherence to treatment, developed a more extensive fungal invasion within eight years, causing portal hypertension due to portal vein thrombosis. This is a rare and serious manifestation. Conclusion: Only six similar reports were identified in the medical literature, through a search in the databases of the Pubmed and Scielo platforms.
Keywords: Paracoccidioidomycosis; Portal hypertension; Paracoccidioides